Learning Without Pressure: How Children Acquire Foreign Languages Through Animated Cartoons - Muhammad Zikrullah (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2021)
In an age where digital media profoundly influences early childhood experiences, the significance of animated cartoons in foreign language acquisition has attracted increased academic attention. Although formal instruction is fundamental to language education, informal, media-based exposure especially via cartoons presents a potentially potent yet underexamined pathway for language acquisition. This study rigorously analyzes 38 peer-reviewed, Scopus-indexed articles to investigate the acquisition of foreign languages by children through animated cartoons, emphasizing the psychological comfort and inherent nature of the learning process. The study utilizes a critical review methodology to synthesize empirical data from applied linguistics, educational psychology, and media studies. The investigation demonstrates that cartoons facilitate quantifiable improvements in vocabulary and phonological awareness, frequently without explicit teaching. Children interact with foreign-language material in a psychologically low-pressure setting, supported by elements such as visual redundancy, repetition, and emotional connections to characters. Contextual factors, including as age, frequency of exposure, and parental mediation, additionally influence learning outcomes. These findings highlight the efficacy of animated cartoons as supplementary resources in early language education, especially in environments with restricted formal instruction. The study enhances the existing literature promoting multimodal, emotionally supportive learning settings and provides practical implications for educators, parents, and policymakers aiming to utilize media for language development.